2020
DOI: 10.1038/s41598-020-62430-z
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazine ring-based Na+/H+ exchanger (NHE) inhibitors potently inhibit cancer cell growth in 3D culture, independent of NHE1

Abstract: the na + /H + exchanger-1 (NHE1) supports tumour growth, making NHE1 inhibitors of interest in anticancer therapy, yet their molecular effects are incompletely characterized. Here, we demonstrate that widely used pyrazinoylguanidine-type NHE1 inhibitors potently inhibit growth and survival of cancer cell spheroids, in a manner unrelated to NHE1 inhibition. Cancer and non-cancer cells were grown as 3-dimensional (3D) spheroids and treated with pyrazinoylguanidine-type (amiloride, 5-(N-ethyl-Nisopropyl)-amilorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 55 publications
0
25
1
Order By: Relevance
“…One such pathway is paraptosis, in which ER and mitochondria dilate in absence of classical features of apoptosis and necrosis [ 187 ]. The process is induced by a number of natural compounds and anticancer drugs [ 188 ], including compounds previously considered specific NHE1 inhibitors [ 189 ] and is of interest in the treatment of cancer cells, which have downregulated apoptotic machinery. Notably, while the mechanisms involved in paraptosis are still incompletely understood, substantial evidence links it to Ca 2+ dysregulation, and also BK channel dysfunction and disturbed K + homeostasis has been suggested [ 188 ].…”
Section: Cancer Cell Functions Driven By Changes In Mitochondrial Architecturementioning
confidence: 99%
“…One such pathway is paraptosis, in which ER and mitochondria dilate in absence of classical features of apoptosis and necrosis [ 187 ]. The process is induced by a number of natural compounds and anticancer drugs [ 188 ], including compounds previously considered specific NHE1 inhibitors [ 189 ] and is of interest in the treatment of cancer cells, which have downregulated apoptotic machinery. Notably, while the mechanisms involved in paraptosis are still incompletely understood, substantial evidence links it to Ca 2+ dysregulation, and also BK channel dysfunction and disturbed K + homeostasis has been suggested [ 188 ].…”
Section: Cancer Cell Functions Driven By Changes In Mitochondrial Architecturementioning
confidence: 99%
“…11 Furthermore, the use of ion transport inhibitors is very common 12,13 but recent studies have reported significant off-target effects of various pHi-lowering drugs. 14,15 Micropipette pHi manipulation techniques are highly specific and adaptable to single-cell analysis. 16 However, micropipette pHi manipulation is technically challenging, has poor temporal control, is damaging to the cell, and is low-throughput.…”
Section: Introductionmentioning
confidence: 99%
“…The work described above suggests that the cell biological and biochemical effects of increased pHi in cancer correlate with and perhaps reinforce transcriptional and proteostatic changes associated with cancer. However, several recent papers that note off-target effects of key pHi manipulating drugs [ 130 , 131 ] have begun to call into question the previous causative role of cytosolic pH in driving tumorigenic phenotypes at the population level. Indeed, the work in this field so far has been crippled by the lack of tools to spatiotemporally manipulate and measure pHi across multiple cancer model systems (cell lines, organoids, and in vivo models) to determine the roles of pHi dynamics across biological scales.…”
Section: Discussionmentioning
confidence: 99%